2021
DOI: 10.1111/jce.15006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acute and long‐term outcomes of Evolution® and TightRail™ mechanical dilator sheaths during transvenous lead extraction

Abstract: Background: Powered transvenous lead extraction (TLE) tools are commonly required to remove the leads with long implant duration due to fibrotic adhesions.However, comparative data are lacking among different types of TLE tools.Aim: To compare the efficacy and safety of two different rotational mechanical dilator sheaths in retrospectively analyzed patients who underwent TLE.Methods and Results: A total of 566 lead extractions from 302 patients using TightRail™ (333 lead extractions from 169 patients) and Evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The clinical success rate was 96.8%, which is comparable to prior studies that have investigated the excimer laser sheath, Cook Evolution mechanical dilator sheath, or the TightRail sheath despite having an average lead age (10.7 years) 4-5 years greater than most of these studies. 2,8,10,12,14,15 Only one MAE was observed during or immediately after TightRail use. In the LExICon (Lead Extraction in the Contemporary Setting Study) which included 1449 consecutive patients undergoing laserassisted lead extraction, the rate of MAEs was 4%.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The clinical success rate was 96.8%, which is comparable to prior studies that have investigated the excimer laser sheath, Cook Evolution mechanical dilator sheath, or the TightRail sheath despite having an average lead age (10.7 years) 4-5 years greater than most of these studies. 2,8,10,12,14,15 Only one MAE was observed during or immediately after TightRail use. In the LExICon (Lead Extraction in the Contemporary Setting Study) which included 1449 consecutive patients undergoing laserassisted lead extraction, the rate of MAEs was 4%.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, most previous studies have focused on TightRail either as a solo tool or as an initial tool. 4,7,9,12 Qin et al 10 described adjunctive TightRail use in 32 leads, which was associated with a 75.8% complete procedural success rate. Thus, our study is unique in that it reports a large number of leads (343) in which the laser and TightRail are used together in a highly effective manner, resulting in a 94.8% complete procedural success rate with adjunctive TightRail use.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the longer TightRail TM , the TightRail TM Sub‐C sheath features a shorter stiffer shaft at the base increasing pushability and stability during the initial phase of the extraction procedure—in conclusion, allowing for an easier handling especially under the clavicle at the vessel entry site while preserving safety. While previous studies demonstrated similar efficacy and safety of both the long versions of mechanical rotational extraction sheaths, 6 there is a lack of data specifically investigating the efficacy of the short TightRail TM Sub‐C sheath. Furthermore, as previously described, the Sub‐C has a more aggressive distal rotating blade compared to the long TightRail TM sheath to overcome calcification at the point of vascular entry of the lead, and therefore evaluation of its safety is of high relevance 10 …”
Section: Discussionmentioning
confidence: 99%
“… 1 Several techniques and tools are used in lead extraction such as traction, locking stylet, sheath and grasping devices, mechanical dilator sheaths, and laser extraction. 2 , 3 Lead extraction can be challenging because of the fibrous adhesions between the lead and cardiovascular structures that develop over time. The application of a laser sheath over the lead during extraction helps release these adhesions by delivering a ring of laser light in pulses to the working section of the sheath.…”
Section: Discussionmentioning
confidence: 99%